ESTROGEN HORMONE PROFILE AND ESTRUS RESPONSE OF THIN TAILED EWES SYNCHRONIZED WITH CONTROLLED INTERNAL DRUG RELEASE - Seraphina Kumala; widya Asmarawati; Ismaya Ismaya; sigit bintara; Riyan Nugroho Aji; Diah Tri Widayati (Universitas Syiah Kuala, 2021)
This research was conducted to identify the estrogen hormone profile and estrus response in the thin tailed ewes synchronized with controlled internal drug release (CIDR) implant. This research was carried out by employing 8 thin tailed ewes, CIDR, and estrogen kit. The ewes were distributed into: 3 ewes as control group and 5 ewes as treated group (with 12 days-CIDR implantation). Ewes were raised in the Sidomukti farm group, Sleman Regency, Yogyakarta. The data obtained were estrogen hormone profile during estrus examined by using ELISA method and estrus response marked with the reddening and oedema of vulva, mucus vaginal discharge, behavioral changes, vaginal pH, and superficial cells population. The data were analyzed by applying independent sample T-test. The result did not show any significant difference (P0.05) in the normal range between the control and CIDR group in estrogen hormone profile, estrus response, and pH level, but showed significant differences with positive correlation (P0.05) in population of superficial cells. In conclusion, CIDR was an effective tool for estrus synchronization at the farmer group, and gave positive estrus response towards thin tailed ewes with estrogen hormone profile, pH level, and superficial cell percentage on the normal range.